TAREKAT ALAWIYYAH DI KALIMANTAN SELATAN: Sebuah Telaah Unsur Neo-Sufisme dalam Tarekat - Abdul Hakim (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2011)
As a known tarekat, the tarekat 'Alawiyah basically insists on planting experience of shariah and noble character. Tarekat Alawiyah in South Kalimantan taught by teacher Bachiet also emphasized the moral aspect of his disciples. Moral formation was through the Majelis taklim assemblies. Among its activities are sympathize widows, orphans and habaib. The establishment of moral and social activity is an essential element in the neo-Sufism. In addition, remembrance and carried muraqabah also an element of neo-Sufism. But the use of the dzikir of isim mufrad and dhamir "Hua" is the influence of philosophical sufism is mostly found in South Kalimantan. Practice of the tarekat by taking account of social activity are part of the neo-Sufism that need to be developed, so that they practice this Sufism (the tarekat) is also directly involved with issues facing today's society.